Bidara leaf extract (Ziziphus mauritiana) inhibits MMP-1 increase and collagen decrease in female Wistar rat skin exposed to UVB and cigarette smoke - Citra Anggraeny; Anak Agung Gde Putra Wiraguna; Gde Ngurah Indraguna Pinatih (Neurologico Spinale Medico Chirurgico, 2021)
Background: Exposure to cigarette smoke and UV-B, can activate enzymes that degrade collagen and inhibit its production through increased levels of MMP-1. Bidara leaves with high content of flavonoids and tannins may prevent damage caused by free radicals. This study aimed to prove the effect of bidara leaf extract in inhibiting the increase in MMP-1 levels and collagen reduction in female Wistar rats skin exposed to UV-B and cigarette smoke. Methods: A randomized posttest-only control group design study was conducted on 30 female Wistar rats, aged 8-10 weeks, weighing 130-150 grams. The rats were divided into three groups: the group without treatment, the base cream, and the 7.5% bidara leaves extract groups. The last two groups were exposed to UV-B light and cigarette smoke. After four weeks of intervention, the back skin tissue was taken to assess collagen amount and MMP-1 levels. Comparative analysis was performed to see the difference between groups. Results: The results showed that the mean levels of MMP-1 in the untreated group were lowest, followed by the bidara leaf extract cream and the base cream group. The mean of collagen amount of bidara leaf extract group was the highest, followed by the base cream and the untreated group. The analysis showed a significant difference in the mean levels of MMP-1 and collagen amount between groups (p<0.05). Conclusion: The 7.5% bidara leaf extract cream inhibited the increase in MMP-1 levels and the decrease in collagen in female Wistar rats exposed to UV-B light and cigarette smoke.